Clonal distribution and intratumour heterogeneity of the B‐cell repertoire in oesophageal squamous cell carcinoma. Issue 3 (19th September 2018) - Zhang, Chaoting; Huang, Hongying; Miao, Yu; Xiong, Hongchao; Lu, Zheming
Abstract: Recent successes in tumour immunotherapies have highlighted the importance of tumour immunity. However, most previous studies to date have focused on T‐cell immune response, although B cells are key players in the core immune network and are associated with T‐cell immune response. Based on our previous study delineating T‐cell receptor (TCR) repertoire in seven patients with oesophageal squamous cell carcinoma (ESCC), this study profiled the B‐cell receptor (BCR) repertoire of multiple tumour regions, adjacent normal tissue, and blood from the same seven patients to reveal the characteristics of B‐cell immunity and the relationship to TCR repertoire in ESCC patients. We found that intratumour BCR repertoire was significantly more oligoclonal than matched adjacent normal tissue or peripheral blood and, moreover, clonal amplification of B cells in multiple tumour regions was significantly heterogeneous, although clonal amplification of the TCR repertoire across different tissue compartments and regions of the same tumour was similar. However, both BCR and TCR repertoires in the tumour microenvironment were distinct from those in adjacent normal tissues and blood, and thus represented a group of B and T cells that were spatially confined to the tumour microenvironment and could react to tumour antigens. Additionally, B‐ and T‐cell clones varying between different tumour regions showed intratumour heterogeneity of B‐ and T‐cell immune response. Thus, multiple tumour biopsies could be essential to comprehensively delineate the adaptive immune response to an individual ESCC. These findings expand our understanding of adaptive anti‐tumour immunity and shed more light on ESCC immunotherapy. This study provides insights into the intratumour heterogeneity of the BCR repertoire as well as the difference and relationship between the BCR and TCR repertoire in ESCC, expanding our understanding of adaptive anti‐tumour immunity and ESCC immunotherapy. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.